Analysis of Factors Associated with Compliance with Mask Use in Pulmonary Tuberculosis Patients at Era Medika Hospital Lung Clinic - Fahjaria, Reni Alif; Reny Mareta Sari (Universitas STRADA Indonesia, 2025)
Pulmonary TB is an infectious disease caused by the bacterium Mycobacterium Tuberculosis. Transmission of Pulmonary TB can be prevented by covering the mouth when coughing or sneezing by using a mask. The purpose of this study was to determine the factors associated with compliance with the use of masks by Pulmonary TB patients at the Lung Polyclinic of Era Medika Hospital. The study design was cross-sectional. This study was conducted by direct observation and collecting data on Pulmonary TB patients at the Lung Polyclinic of Era Medika Hospital simultaneously. The population of this study were all patients at the Lung Polyclinic of Era Medika Hospital. The sample used was some of the patients at the Lung Polyclinic of Era Medika Hospital who were diagnosed with Pulmonary TB as many as 75 patients using the Accidental Sampling technique. The independent variables of this study were patient attitudes, patient motivation, patient perceptions, and the availability of masks. The dependent variable of this study was compliance with the use of masks. The study used a questionnaire sheet. Data analysis used univariate analysis and bivariate analysisand using statistical testsPearson Chi-Square. The results of the study explain that there is a relationship between attitudes and compliance with mask use (p-value 0.000) the frequency of respondents with positive attitudes was 53 respondents (69.3%) and respondents who comply with mask use were 50 respondents (66.7%). There is no relationship between patient motivation and compliance with mask use (p-value 0.477) where the frequency of patient motivation is high 74 respondents (98.7%). There is a relationship between patient perception and compliance with mask use (p-value 0.000) with a frequency of positive perception of 42 respondents (56%). There is a relationship between the availability of masks and patient compliance with mask use (p-value 0.000) with the frequency of respondents providing masks as many as 49 respondents (65.3%). It is hoped that patients will implement education related to compliance with mask use that has been provided by doctors at the Lung Polyclinic, Era Medika Hospital.